2018
DOI: 10.1371/journal.pone.0202970
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alpha-(1,2)-fucosyltransferase genotype variants on plasma metabolome, immune responses and gastrointestinal bacterial enumeration of pigs pre- and post-weaning

Abstract: In pigs, the alpha-(1,2) fucosyltransferase (FUT1) gene has been highlighted for its properties in controlling the intestinal expression of enterotoxigenic E. coli (ETEC) F18 receptors; a pathogen causing edema disease and post-weaning diarrhoea. In this study, we hypothesized that pigs with different genotypes (ETEC F18 resistant (FUT1AA) versus susceptible (FUT1AG)) differed in following systemic and enteric responses: growth performance, plasma metabolic profiles, expression of candidate genes for intestina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 55 publications
2
19
0
Order By: Relevance
“…Little information is reported on the FUT1 effect on intestinal microbiota. However, our results reinforce the observations reported by Poulsen et al () in which FUT1 AG ETEC F18 susceptible piglets showed a higher number of non‐beneficial bacteria, including haemolytic bacteria, both in faeces and in digesta, and of Enterobacteriaceae in digesta than FUT1 AA piglets, even without the presences of diarrhoea. Thus, our results suggest that FUT1 genotype is not only associated with ETEC F18 resistance but can also play a role in the modulation of the commensal gut bacteria in healthy pigs.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Little information is reported on the FUT1 effect on intestinal microbiota. However, our results reinforce the observations reported by Poulsen et al () in which FUT1 AG ETEC F18 susceptible piglets showed a higher number of non‐beneficial bacteria, including haemolytic bacteria, both in faeces and in digesta, and of Enterobacteriaceae in digesta than FUT1 AA piglets, even without the presences of diarrhoea. Thus, our results suggest that FUT1 genotype is not only associated with ETEC F18 resistance but can also play a role in the modulation of the commensal gut bacteria in healthy pigs.…”
Section: Discussionsupporting
confidence: 92%
“…Those differences in the intestinal characteristics can, therefore, concur to determine differences in piglets’ metabolism (Poulsen et al, ) and in piglet nutritional requirement (Trevisi et al, ) and result in different growth performance as already reported by Fontanesi et al. () for MUC4 and by Bao et al () for FUT1 in adult pigs.…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations